2015
DOI: 10.1136/postgradmedj-2015-133358
|View full text |Cite
|
Sign up to set email alerts
|

Learning theory and its application to the use of social media in medical education

Abstract: Background There is rapidly increasing pressure to employ social media in medical education, but a review of the literature demonstrates that its value and role are uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 13 publications
(11 reference statements)
0
66
0
1
Order By: Relevance
“…Previous ways of navigating and filtering available information are likely to prove ineffective in these new contexts. The ability to access relevant information and harness the resources offered by the views and opinions of others have become important skills particularly as the need for lifelong learning, both formal and informal is increasingly recognised by individuals, organisations and institutions (Cheston et al, 2013, Flynn et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous ways of navigating and filtering available information are likely to prove ineffective in these new contexts. The ability to access relevant information and harness the resources offered by the views and opinions of others have become important skills particularly as the need for lifelong learning, both formal and informal is increasingly recognised by individuals, organisations and institutions (Cheston et al, 2013, Flynn et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…2012. It is beginning to be recognised by medical educators (Sandars and Morrison, 2007, Sandars and Haythornthwaite, 2007, Mehta et al, 2013, Lau, 2014, Downes, 2015, Flynn et al, 2015 due to its' claim to provide a lens through which teaching and learning using digital technologies can be better understood and managed. This paper aims to examine connectivism and its potential application in medical education.…”
Section: Introductionmentioning
confidence: 99%
“…They are centred on the fact that students subjectively construct knowledge themselves. Flynn et al, (2015) identified the Social Development Theory and Communities of Practice to be the most important Constructivism theories linked to social media whilst Hennessy et al, (2016) highlight the importance of a Zone of Proximal development (Table 2). With the integration of social media into medical education, learning has become a more social process because it is user-generated and Whyte W, Hennessy C MedEdPublish https://doi.org/10.15694/mep.2017.000083 collaborative.…”
Section: Community and Interactivitymentioning
confidence: 99%
“…Whilst they believe that it is the lecturer's role to teach students how best to use social media, they found that the staff members did not actually have the skill set to do so. If social media is misused then it can negatively impact the students learning due to disrupted workflow and the potential to distract (Flynn et al, 2015;Madanick, 2015). If social media is to be successfully integrated into medical education than this mismatch must be addressed.…”
Section: Role Of Facultymentioning
confidence: 99%
See 1 more Smart Citation